Health related quality of life assessment in acute coronary syndrome patients : the effectiveness of early phase I cardiac rehabilitation - Lawrence, Anchah; Mohamed Azmi, Hassali; Melissa Lim, Siaw Han; Mohamed Izham, Mohamed Ibrahim; Sim, Kui Hian; Ong, Tiong Kiam (BioMed Central Ltd., 2017)
Background: Acute Coronary Syndrome (ACS) is one of the most burdensome cardiovascular diseases in terms of the cost of interventions. The Cardiac Rehabilitation Programme (CRP) is well-established in improving clinical outcomes but the assessment of actual clinical improvement is challenging, especially when considering pharmaceutical care (PC) values in phase I CRP during admission and upon discharge from hospital and phase II outpatient interventions. This study explores the impact of pharmacists’ interventions in the early stages of CRP on humanistic outcomes and follow-up at a referral hospital in Malaysia. Methods: We recruited 112 patients who were newly diagnosed with ACS and treated at the referral hospital, Sarawak General Hospital, Malaysia. In the intervention group (modified CRP), all medication was reviewed by the clinical pharmacists, focusing on drug indication; understanding of secondary prevention therapy and adherence to treatment strategy. We compared the “pre-post” quality of life (QoL) of three groups (intervention, conventional and control) at baseline, 6 months and 12 months post-discharge with Malaysian norms. QoL data was obtained using a validated version of Short-Form 36 Questionnaire (SF-36). Analysis of variance (ANOVA) with repeated measure tests was used to compare the mean differences of scores over time. Results: A pre-post quasi-experimental non-equivalent group comparison design was applied to 112 patients who were followed up for one year. At baseline, the physical and mental health summaries reported poor outcomes in all three groups. However, these improved gradually but significantly over time. After the 6-month follow-up, the physical component summary reported in the modified CRP (MCRP) participants was higher, with a mean difference of 8.02 (p = 0.015) but worse in the mental component summary, with a mean difference of −4.13. At the 12-month follow-up, the MCRP participants performed better in their physical component (PCS) than those in the CCRP and control groups, with a mean difference of 11.46 (p = 0.008), 10.96 (p = 0.002) and 6.41 (p = 0.006) respectively. Comparing the changes over time for minimal important differences (MICD), the MCRP group showed better social functioning than the CCRP and control groups with mean differences of 20.53 (p = 0.03), 14.47 and 8.8, respectively. In role emotional subscales all three groups showed significant improvement in MCID with mean differences of 30.96 (p = 0.048), 31.58 (p = 0.022) and 37.04 (p < 0.001) respectively. Conclusion: Our results showed that pharmaceutical care intervention significantly improved HRQoL. The study also highlights the importance of early rehabilitation in the hospital setting. The MCRP group consistently showed better QoL, was more highly motivated and benefitted most from the CRP. Trial registration: Medical Research and Ethics Committee (MREC) Ministry of Health Malaysia, November 2007, NMRR-08-246-1401. Keywords: Clinical pharmacy, Cardiac rehabilitation programme, Quality of life, SF-36, Acute coronary syndrome